The Effect of the Write Pair Switch Method on Student’s Reasoning Ability Based on Initial Ability - Madaling Madaling; Rissa Megavitry; Mas’ud Muhammadiah (Journal on Education, 2023)
abilities of students who studied with conventional methods and those who studied with the write-pair-switch method. This study was carried out at one of the public high schools for the 2022–2023 academic year. A posttest-only control design was used in the quasi-experimental research methodology. The study sample consisted of 85 students, consisting of 43 control class students and 42 experimental class students. Each class is subdivided into 3 levels based on their initial mathematical ability, namely low, medium, and high levels. Two-way ANOVA is the method of data analysis employed. The findings indicated that students' mathematical reasoning skills were impacted by the learning strategies used. The degree of a student's initial mathematical proficiency affects their capacity for mathematical reasoning. There is no relationship between learning strategies and the degree of pupils' innate mathematical competence in terms of their capacity for mathematical reasoning.